Effects of extraction methods on the fuel characteristics and diesel engine performances of jatropha curcas biodiesel - W., Anggono; M. M., Noor; S., Liao; K., Sanka; G. J., Gotama; Sutrisno, .; F. D., Suprianto (Springer Netherlands, 2022)
The development of high-quality biodiesel fuel has become more relevant due to the limited reserve and environmental effects of fossil fuel. In this study, oils derived from Jatropha curcas seeds through two extraction methods (soxhlet and cold-press) were compared. The fuel characteristics investigation suggested that methyl ester derived from oil extracted with the soxhlet method has lower viscosity, higher calculated cetane index, and slightly higher sulphur content. Comparison on the fuel characteristics with biodiesel standards showed that the methyl esters still had substantial amount of methanol and water due to low temperature during transesterification. The oils were also compared for their engine performances in a diesel engine under engine rotation of 1800 to 3000 RPM by blending derived methyl ester with pure petro-diesel to create B20 biodiesel. On average, B20 from soxhlet extraction has 3.86% higher power output, 3.55% higher torque, 3.4% higher BMEP, and 5.89% lower BSFC compared to cold-press. The extraction method affects the fuel characteristics of the methyl ester and the engine performances of the B20 biodiesel.